Tuva and the USSR: the process of political integration - Harunova, Marianna M.-B. (The New Research of Tuva, 2009)
Article unveils political preconditions of Tuva’s joining the USSR and entailing reformation of the government and public organizations. Attention is drawn to the formation of the subsidy-dependant budget of the Soviet Tuva within the political system of the USSR.